Newsletter No. 28 - (:unkn) unknown (My University, 2010)
Contains news on the progress of Wave 4; Wave 5 development; Respondent focus groups; LSAC Annual statistical report; the NAPLAN data linkage; the 11th Australian Institute of Family Studies Conference and associated data user training; updates on Wave 3.5, Wave 5; Life at 5.
28
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology